Competencia desleal y resguardo de los secretos empresariales - Sosa Huapaya, Alex (2015)
The Law of Supression of Unfair Competition, approved by Legislative Decree 1044, tries to avoid confusions about what is protected as a trade secret and what cases of misappropriation should be sanctioned.In this article, the author questions the interpretation and application that has beenconsistently employed, in many cases, to some of the terms contained in the aforementioned law.For that purpose, the author explains the meaning of the trade secret and other related terms, such as prohibited competition and concurrent purposes. He then proceeds to elaborate an analysis about the economic function of protecting trade secrets and what should be the correct application of the Law of Supression of Unfair Competition.